The Role of Cognition When Executing an Online, Visually Evoked Adjustment to an Obstacle Circumvention Strategy. Issue 2 (7th February 2022) - Pitman, Jenna; Vallis, Lori Ann
Abstract: We know that performing simultaneous cognitive tasks during locomotion results in reduced performance on either or both tasks, however the role of the cognitive system in the execution of last-minute changes to ongoing adaptive locomotor tasks is not fully understood. Nineteen participants were initially cued to circumvent to left, right, or step over an obstacle while an auditory cognitive task was simultaneously presented. In half of the trials, no change in avoidance strategy was required; in the remaining trials, participants were visually cued two steps in advance to execute a new circumvention strategy. Participants decreased gait velocity and increased cognitive task response times when executing changes in strategy, highlighting the important role the cognitive system plays in these complex tasks.